Planned preventive maintenance (PPM) effects on overall equipment effectiveness (OEE): a case study in Malaysian industry - Khalili, Amjad; Ismail, Md Yusof; Ruzman, Muhammad Arif (Inderscience Publishers, 2022)
Total productive maintenance (TPM) and planned preventive maintenance (PPM) has same drive of implementation. This paper focuses on evaluation of the effectiveness of batching plant machine, the overall equipment effectiveness (OEE) before and after implementation of PPM was compared to show the effect of planned maintenance to the effectiveness of the machine. The primary data reflected before and after implementation issues for breakdown time was gathered from selected industry to show the effect on availability of the equipment, performance efficiency of the process and rate of quality products. Both SPSS 25 and Excel were utilised for analysis. Results implied that OEE display an improvement by the reduction of the OEE percentage from 68.3% to 57.5%. These indicate that implementation of PPM does have an effect on availability of the equipment, performance efficiency of the process and rate of quality products and does improve the OEE at the selected company.